Match between UMP furniture dimension and student's anthropometry - Wahidah, Haron (2007)
Ergonomic issue is one of the important issues not only in workstation but also in educational institution since it is related to the human. Chair is one of furniture that is used widely in our daily life in purpose of sitting. Having a match chair that applied ergonomic is an important aspect to look at to avoid bad effect such as back pain and should provide comfortness and safety to the user. This project is conducted to determine whether the UMP chair in the student hostel match with the students' anthropometry or not. The seat height and seat depth of the chair is measured and the student popliteal height and buttock-popliteal length is analyzed. From the analysis, it can be concluded that the chair in student hostel did not match with the student. As a solution, an adjustable chair which applied ergonomic is designed to match the UMP students' anthropometry to optimize safety, comfort and prevent back pain.